Suborder Oribatida van der Hammen, 1968. In: Zhang, Z.-Q. (Ed.) Animal biodiversity: An outline of higher-level classification and survey of taxonomic richness - Schatz, Heinrich; Behan-Palletier, Valerie M.; Oconnor, Barry M.; Norton, Roy A. (Zootaxa, 2011)
-